Administrative culture and political change [review of] - Belen, Nelia R. (1996)
A review of Amelia P. Varela, Administrative Culture and Political Change (Quezont City: College of Public Administration, University of the Philippines, 1996). xi + 325pp.
Keywords: Book reviews